Growth of ultrathin Cr films on benzene-covered Ni(111) - Sklarek, Werner; Held, Georg; Ammon, Christian; Steinrück, Hans-Peter (Applied Surface Science, 1999)
Using X-ray photoelectron spectroscopy (XPS) and temperature programmed desorption (TPD) we studied the properties of thin Cr films in the nominal coverage range between 0.13 and 4 monolayers (ML), which were evaporated onto a Ni(111) surface pre-covered with up to 14 ML benzene. Evaporation of small amounts of Cr (< 0.5 ML) onto thick benzene layers (> 4 ML) at 100 K leads to the formation of non-metallic bis(benzene)chromium (Cr(CH)) rather than condensation of small clusters in the benzene matrix, as can be seen from the positions and shapes of the Cr 2p peaks in XPS. Upon annealing to 400 K these films transform into metallic Cr as is indicated by a Cr 2p peak shift of -0.8 eV, and significant changes in the peak shapes. For 0.5-2 ML a metallic Cr species, in addition to the non-metallic species, is already seen at 100 K. For higher coverages > 2 ML only the metallic species is seen in XPS and the Cr 2p peak shape does then not change upon annealing. The development of the C 1s spectra upon annealing reveals that there is a significant amount of benzene buried under the Cr layer, which is partially dissociated, depending on the annealing temperature and the Cr coverage.